A Meta-Analysis of Factors Associated with the Practice of Sufficiency Economy Philosophy in Daily Life - Tongsamsi, Isara (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2023)
This meta-analysis research aimed to explore research characteristics, compare differences in research characteristics, and analyze standard indexes of factors associated with the practice of the sufficiency economy philosophy in daily life. There were 73 quantitative research reports, that compared or analyzed the relationship between variables, conducted during 2012-2021. The instruments used in the study were a research quality assessment form and a summary of research characteristics form. Both forms were approved by three experts for the content validity testing. All of the data were calculated by using the meta-analysis method of Rosenthal and Hedges, in which the values of standard index obtained as 233. The data were analyzed using the Jamovi program, MAJOR-Meta-Analysis for JAMOVI as the supporting program, and R program. The results showed that the research characteristics consisted of three aspects including general characteristics, substantive of the research, and methodological characteristics. It was found that there was no characteristics that could cause differences in standard index averages. For the results of a Meta-Analysis, it was discovered that factors that were positively correlated with the practice of the sufficiency economy philosophy in daily life would include psychological state factors (r=.52, p<.001), situational factors (r=.36, p<.001), psychological characteristics factors (r=.21, p<.001), and biosocial and background factors (r=.11, p<.001), respectively.